The Theory of Nullity in Islamic Jurisprudence: A Comparative Approach Through the Lens of Disposing of Another’s Property - Ismaeel Alhadidi; Ghofran Hilal; Thawab Hilal (Faculty of Sharia UIN Kiai Ageng Muhammad Besari Ponorogo, 2026)
This article aims to conduct a comparative analysis of contract cancellation theories in the Jordanian and French legal systems, focusing on contracts involving the illegal transfer of another party's property. This study examines the fundamental differences between the concepts of absolute and relative nullity in French law and the Jordanian legal approach rooted in Islamic jurisprudence, particularly through the concepts of “suspension” and “non-binding contracts.” The method used is normative legal research with a philosophical-comparative approach. The analysis was conducted on the main provisions of Jordanian legislation and legislative and judicial practices in France, accompanied by a doctrinal study of the theories of cancellation and protection of third-party rights in both legal systems. The findings of the study show that French law makes a clear distinction between absolute and relative nullity, while Jordanian law rejects the concept of relative nullity and replaces it with a suspension mechanism. The theory of suspension, inspired by Islamic law, is considered more flexible and equitable, especially in protecting the property rights of third parties, including vulnerable persons, and more adaptive to the complexity of modern transactions. The practical contribution of this research is a recommendation for legislative reform in Jordan to expand the subjects entitled to cancel suspended contracts, as well as an encouragement for civil law systems to consider adopting the theory of suspension as an alternative to relative nullity. The integration of this concept is believed to increase legal certainty and the protection of individual rights in complex contract disputes.